The relationship between host country factors and FDI motivations: Evidence from Korean FDI in ASEAN countries - Thuy Thi Nguyen; Hanbe Cho (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
The literature suggests that various host country factors influence firms’ decisions to invest abroad, but there is a low consensus in empirical research, as results vary across contexts. However, empirical studies typically examine the relationship between overall FDI and host country factors, ignoring the differences in investment motivations of multinational enterprises. Firms may have different motivations, such as market seeking or efficiency seeking, and thus are attracted by other factors in host countries. Using data from the Korean Export-Import (EXIM) Bank and fixed-effect models, this study examines how the determinants of FDI vary based on different investment motivations from South Korea to nine ASEAN countries (excluding Brunei). Economic growth deters low-wage-seeking and resource-seeking FDI but does not impact other FDI motivations. However, some factors commonly believed to influence specific motivations affect FDI similarly across motivations. For example, GDP and wages consistently emerge as determinants across different types of investment. Our findings thus contribute to the literature on the determinants associated with various FDI motivations. However, as our study covers a limited set of host country factors and is focused on a specific context, further and more comprehensive investigations are needed in the future.